Business Dispute Resolution Outside the Court: An Analysis of Arbitration and Mediation in Indonesia - Muhammad Gustiar; Muh Sutri Mansyah; La Ode Bunga Ali (PT Justitia Legal Research, 2025)
The increasing complexity of business activities in Indonesia has resulted in a growing number of commercial disputes that require effective and efficient resolution mechanisms. Litigation through state courts is often considered inadequate for business disputes due to lengthy procedures, high costs, rigid formalities, and potential damage to business relationships. This study examines the effectiveness of arbitration and mediation as alternative dispute resolution mechanisms in resolving business disputes in Indonesia. Using a normative juridical research method, this paper analyzes statutory regulations, particularly Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, supported by legal doctrines and relevant scholarly works from Indonesian legal journals. The findings indicate that arbitration provides legal certainty through binding and enforceable decisions, making it suitable for complex commercial disputes, while mediation offers flexibility and relationship-oriented solutions that support the continuity of business cooperation. However, the study also identifies several challenges, including limited awareness among business actors, enforcement issues, and institutional constraints that hinder the optimal implementation of both mechanisms. This paper concludes that arbitration and mediation should be applied in a complementary manner rather than as competing mechanisms. Strengthening legal awareness, institutional capacity, and contractual design is essential to enhance the effectiveness of arbitration and mediation in supporting a stable and sustainable business dispute resolution system in Indonesia.